Additive-assisted regioselective 1,3-dipolar cycloaddition of azomethine ylides with benzylideneacetone - Peng, Chuqin; Ren, Jiwei; Xiao, Jun-An; Zhang, Honggang; Yang, Hua; Luo, Yiming (Beilstein Journal of Organic Chemistry, 2014)
1,3-Dipolar cycloadditions of isatins, benzylamine and benzylideneacetones were studied to prepare a series of novel spiropyrrolidine-oxindoles – 4′-acetyl-3′,5′-diarylspiro[indoline-3,2′-pyrrolidin]-2-ones and 3′-acetyl-4′,5′-diarylspiro[indoline-3,2′-pyrrolidine]-2-ones in good yields of up to 94% and with good regioselectivities. Regioselectivities are reversible by the addition of water or 4-nitrobenzoic acid, respectively. The substituent effects on the regioselectivity were also investigated.
Keywords: 1,3-dipolar cycloaddition; azomethine ylide; regioselectivity; spirooxindole